EXCHANGE OF TAX INFORMATION IN THE EUROPEAN UNION: LEGAL INNOVATIONS AND PECULIARITIES - M. S. PEKARSKAYA (Московский журнал международного права, 2018)
INTRODUCTION. The article presents peculiarities of exchange of tax information in the European Union. The author analyses provisions of European Union instruments related to exchange of tax information performed on request, spontaneously or automatically. Special attention is paid to the analysis of legal developments of the Council Directive № 2011/16/EU of 15 February 2011 "On administrative cooperation in the field of taxation and repealing Directive 77/799/EEC”.MATERIALS AND METHODS. Materials used for the analysis include legal writings of Russian and foreign researchers in the field of European tax law as well as current regional European Union instruments and multinational acts devoted to the legal regulation of exchange of tax information. Methodological procedures of the research include general and specific scientific methods of enquiry (dialectical method, methods of analysis and synthesis, deduction, induction, comparative-legal and historicallegal methods).RESEARCH RESULTS. While analyzing, the author evaluates the significance of each form of exchange of tax information for combating tax crimes such as tax fraud, tax avoidance and aggressive tax planning. The author examines the regional European Union instruments devoted to the legal regulation of exchange of tax information in comparison with the multinational acts and global trends dedicated to the same issue.DISCUSSION AND CONCLUSIONS. In this article the author draws attention to the peculiarities of exchange of tax information in the European Union. The article deals with the provisions of regional European Union instruments related to exchange of tax information performed in all three forms. Relying on the doctrine and international documents, the author characterizes rules of exchange of tax information in the European Union, especially in terms of their legal developments, and estimates the readiness of the European Union member states to implement the above-mentioned legal norms.